Renin-Angiotensin System Induced Secondary Hypertension: The Alteration of Kidney Function and Structure - Zahra Pezeshki; Mehdi Nematbakhsh (International Journal of Nephrology)
Long-term hypertension is known as a major risk factor for cardiovascular and chronic kidney disease (CKD). The Renin-angiotensin system (RAS) plays a key role in hypertension pathogenesis. Angiotensin II (Ang II) enhancement in Ang II-dependent hypertension leads to progressive CKD and kidney fibrosis. In the two-kidney one-clip model (2K1C), more renin is synthesized in the principal cells of the collecting duct than juxtaglomerular cells (JGCs). An increase of renal Ang I and Ang II levels and a decrease of renal cortical and medullary Ang 1–7 occur in both kidneys of the 2K1C hypertensive rat model. In addition, the activity of the angiotensin-converting enzyme (ACE) increases, while ACE2’s activity decreases in the medullary region of both kidneys in the 2K1C hypertensive model. Also, the renal prolyl carboxypeptidase (PrCP) expression and its activity reduce in the clipped kidneys. The imbalance in the production of renal ACE, ACE2, and PrCP expression causes the progression of renal injury. Intrarenal angiotensinogen (AGT) expression and urine AGT (uAGT) excretion rates in the unclipped kidney are greater than the clipped kidney in the 2K1C hypertensive rat model. The enhancement of Ang II in the clipped kidney is related to renin secretion, while the elevation of intrarenal Ang II in the unclipped kidney is related to stimulation of AGT mRNA and protein in proximal tubule cells by a direct effect of systemic Ang II level. Ang II-dependent hypertension enhances macrophages and T-cell infiltration into the kidney which increases cytokines, and AGT synthesis in proximal tubules is stimulated via cytokines. Accumulation of inflammatory cells in the kidney aggravates hypertension and renal damage. Moreover, Ang II-dependent hypertension alters renal Ang II type 1 & 2 receptors (AT1R & AT2R) and Mas receptor (MasR) expression, and the renal interstitial fluid bradykinin, nitric oxide, and cGMP response to AT1R, AT2R, or BK B2-receptor antagonists. Based on a variety of sources including PubMed, Google Scholar, Scopus, and Science-Direct, in the current review, we will discuss the role of RAS-induced secondary hypertension on the alteration of renal function.